INSTITUTIONAL MODELING IN TOURISM DEVELOPMENT IN CIBUNTU TOURISM VILLAGE, KUNINGAN: AN ACTOR ANALYSIS - Brantas Brantas (SEAN Institute, 2023)
The existence of parties who have an interest in a tourist destination is vital because of its function as a controller for the diversity and complexity of the tourism industry, including in tourist villages. Therefore, it is necessary to review how far stakeholder involvement is as a form of actualization of an institution in tourist destinations, especially rural tourism. This study uses a qualitative method that is adapted to the concept of descriptive research by collecting data from semi-structured interviews with several related parties. The results of the discussion and discussion indicate that from the case study in the Cibuntu Tourism Village, the implementation of tourism activities is centralized to stakeholders who are key players, namely the Cibuntu Village Government, Pokdarwis, and BUMDES which regulate all policies and programs. Meanwhile, other stakeholders are divided into subject categories, crowd and contest setters whose existence and functionality need to be maximized.